2017
DOI: 10.1111/lang.12277
|View full text |Cite|
|
Sign up to set email alerts
|

A Usage‐Based Approach to Preposition Placement in English as a Second Language

Abstract: This study examined the acquisition of preposition placement in English as a second language from a usage-based perspective. German and Chinese learners of English and English native speakers rated the acceptability of English oblique wh relative clauses in a magnitude estimation task. Results indicated that acceptability depended on interactions among preposition fronting and stranding, participant group, participants' first language, and their English proficiency. Most importantly, while stranding was more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 64 publications
0
9
0
1
Order By: Relevance
“…However, their similar performance on idiosyncratic the cues and idiosyncratic Ø cues suggested that they had not been able to attune to the idiosyncrasy of entity names in their specific contexts of usage. The lack of contextualised constructional knowledge (the ability to associate constructions to particular contexts) constituted one of the major knowledge gaps between native speakers and L2 learners (Ellis et al 2008;Jach 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, their similar performance on idiosyncratic the cues and idiosyncratic Ø cues suggested that they had not been able to attune to the idiosyncrasy of entity names in their specific contexts of usage. The lack of contextualised constructional knowledge (the ability to associate constructions to particular contexts) constituted one of the major knowledge gaps between native speakers and L2 learners (Ellis et al 2008;Jach 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To do well on this test, participants had to derive an abstract representation of the word order patterns underlying the training sentences. However, to arrive at this level of representation, a critical mass of exposure is required (Tomasello, 2003; Ambridge and Lieven, 2011; Jach, 2018), which the training phase in this experiment might not have provided. Further, it is worth remembering that a small learning effect for syntax is in line with Rebuschat and Williams (2012) and Tagarelli et al (2011), who investigated the incidental learning of the same word order patterns (though without pseudowords).…”
Section: Discussionmentioning
confidence: 99%
“…A corollary of these shared assumptions is that mental grammar emerges out of concrete experience with language (Bybee 2006), meaning that "language acquisition happens in and through use" (Ortega 2014: 193). Researchers adopting a usage-based approach within SLA (e.g., Cadierno and Eskildsen 2015; Ellis and Wulff 2015;Ortega et al 2016;Jach 2018) view language learning as a situated, embodied process in which learners engage (via implicit learning mechanisms) with input, showing sensitivity to various patterns and regularities present in the target language. Characteristics of the input that tend to facilitate learning include higher frequency and greater salience of forms (i.e., sounds, words, constructions), as well as reliable mappings between forms and their functions (Ellis et al 2016).…”
Section: Data-driven Approaches In Slamentioning
confidence: 99%